2020
DOI: 10.1002/dta.2871
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bitter orange dietary supplements for natural and synthetic phenethylamines by LC–MS/MS

Abstract: Citrus aurantium, commonly known as bitter orange, is a popular dietary supplement ingredient sold worldwide. Bitter orange supplements are sold primarily as weight management and sports performance products and have gained popularity after Ephedra products were banned from the US market. Supplements containing synephrine are reported to exhibit adverse cardiovascular effects especially in the presence of caffeine. In this study, an LC–MS/MS method was established to quantify five natural amines (synephrine, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Dutch investigators in 2013 identified 19 mg to 39 mg deterenol combined with other stimulants in Dexaprine (iForce Nutrition) and found this product to be associated with a series of serious adverse events including nausea, vomiting, agitation, palpitations, chest pain and cardiac arrest [4]. Since 2018, three investigations have confirmed the presence of deterenol in supplements available in the US ranging in doses from 20 to 76 mg per serving [7][8][9]. One of these studies was performed by the FDA's analytic chemists [9]; nevertheless, we are not aware of any enforcement action by the agency to eliminate deterenol from dietary supplements or warn consumers of the stimulant's presence in supplements.…”
Section: Deterenol (Isopropyloctopamine)mentioning
confidence: 99%
See 2 more Smart Citations
“…Dutch investigators in 2013 identified 19 mg to 39 mg deterenol combined with other stimulants in Dexaprine (iForce Nutrition) and found this product to be associated with a series of serious adverse events including nausea, vomiting, agitation, palpitations, chest pain and cardiac arrest [4]. Since 2018, three investigations have confirmed the presence of deterenol in supplements available in the US ranging in doses from 20 to 76 mg per serving [7][8][9]. One of these studies was performed by the FDA's analytic chemists [9]; nevertheless, we are not aware of any enforcement action by the agency to eliminate deterenol from dietary supplements or warn consumers of the stimulant's presence in supplements.…”
Section: Deterenol (Isopropyloctopamine)mentioning
confidence: 99%
“…Since 2018, three investigations have confirmed the presence of deterenol in supplements available in the US ranging in doses from 20 to 76 mg per serving [7][8][9]. One of these studies was performed by the FDA's analytic chemists [9]; nevertheless, we are not aware of any enforcement action by the agency to eliminate deterenol from dietary supplements or warn consumers of the stimulant's presence in supplements.…”
Section: Deterenol (Isopropyloctopamine)mentioning
confidence: 99%
See 1 more Smart Citation
“…Octopamine and methylsynephrine are recognized not only as monitored substance but also as doping agents from the group S6 – Stimulants. An example of disqualification for unintended doping in 2013 was the female sprinter Sherone Simpson, as the anti‐doping tests performed on her showed the presence of methylsynephrine, which came from the food supplement she was using [211–213] …”
Section: Ingredients Prohibited By Wadamentioning
confidence: 99%
“…However, WADA specifies that ‘ and other substances with a similar chemical structure or similar biological effect(s) are also prohibited ’. As described in the following sections, the excessive use of certain substances present in dietary supplements by professional athletes has forced WADA to adapt and update its regulations to the current anti‐doping needs [13,211–213] …”
Section: Ingredients Prohibited By Wadamentioning
confidence: 99%